Perceptions of Adolescent Health Care Services in The Era Society 5.0 for Darussalam Health Vocational School Students - Marchamah, Dwi Nur Siti; Dewi, Restu Ayu Eka Pustika; Ersalina, Fadhila Rahma (Lambung Mangkurat, 2024)
Adolescent care health services program are less equitable and optimal. Increasing human resources in the health sector, and health facilities are also needed to support this program. The research aims to determine the perceptions of adolescent healthcare services in the era Society 5.0. This type of research is quantitative descriptive, with a cross-sectional design. Sampling using the Slovin formula was 88 people. Data collection uses a questionnaire. The research results revealed that health workers have good knowledge about various adolescent problems, can help adolescents solve their health problems, and have a pleasant attitude when dealing with or serving adolescents. The health center provides a room to ensure adolescents’ privacy, health workers will be able to recognize all the problems adolescents are experiencing, adolescents will feel comfortable, and adolescents can be served quickly. The community health center's suggestions can increase efforts to develop adolescent care health service programs through online service websites so that implementation targets are met in schools. Apart from that, adolescent empowerment efforts are also needed to support the success of the program.